2009
DOI: 10.3109/11038120902795441
|View full text |Cite
|
Sign up to set email alerts
|

Is length of experience an appropriate criterion to identify level of expertise?

Abstract: Clinical experience plays an important role in the development of expertise, particularly when coupled with reflection on practice. There is debate, however, regarding the amount of clinical experience that is required to become an expert. Various lengths of practice have been suggested as suitable for determining expertise, ranging from five years to 15 years. This study aimed to investigate the association between length of experience and therapists' level of expertise in the field of cerebral palsy with upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In our study, however, the only statistically significant difference in CSI was between novice and experienced therapists; the CSI scores of therapists at the intermediate experience level did not differ significantly from those of therapists at either of the other experience levels. Rassafiani (2009) investigated the relationship between occupational therapists' length of experience and level of expertise by reanalyzing their treatment recommendations for hypothetical clients with cerebral palsy from two previous studies. He found no significant association between years of experience and expertise and concluded that the development of expertise is multifaceted and includes reflection, observation of expert practice, and opportunities for feedback.…”
Section: Comparisons Of Intuition and Ei By Gender And Experiencementioning
confidence: 99%
“…In our study, however, the only statistically significant difference in CSI was between novice and experienced therapists; the CSI scores of therapists at the intermediate experience level did not differ significantly from those of therapists at either of the other experience levels. Rassafiani (2009) investigated the relationship between occupational therapists' length of experience and level of expertise by reanalyzing their treatment recommendations for hypothetical clients with cerebral palsy from two previous studies. He found no significant association between years of experience and expertise and concluded that the development of expertise is multifaceted and includes reflection, observation of expert practice, and opportunities for feedback.…”
Section: Comparisons Of Intuition and Ei By Gender And Experiencementioning
confidence: 99%
“…There is general consensus that thinking changes with experience and expertise [47][48][49][50][51][52][53][54][55][56]. One benefit of this change is that experienced clinicians often recognize similar situations (e.g., familiar problems) more quickly [57].…”
Section: Problem Solving In Medicinementioning
confidence: 99%
“…Much of the understanding of what constitutes an expert is built on the work of Dreyfus and Dreyfus's () model of skills acquisition via the work of Benner (). The major determinant of expertise in the occupational therapy research literature seems to be length of service (Kuipers & Grice, ), although Rassafiani () and others (Weiss, Shanteau & Harries, ) have demonstrated no correlation between length of experience and expertise. Dreyfus and Dreyfus's () model was based on their work with military pilots, a profession where a longstanding perception of expertise related to flight time is existent.…”
Section: Expert: the Criteriamentioning
confidence: 99%
“…While Benner () was quite prescriptive about relating skills acquisition to duration of experience in new graduates, she was very careful not to do so when describing experts, stating quite explicitly ‘experience is not the mere passage of time or longevity’ (Benner, , p. 407). Subsequent to Benner's original work, other authors (cited in Rassafiani, ) have, perhaps misguidedly, extrapolated from her work to suggest somewhat arbitrary durations of service concomitant with the term ‘expert’. However, drawing on Benner's original work and best evidence, duration of service should not be considered as a criterion for judging expertise and, for example, for the purposes of conducting research into the phenomena, the term expert should be associated with characteristics or criteria other than simply length of experience.…”
Section: Expert: the Criteriamentioning
confidence: 99%